Acute tracheal narrowing presumptively associated with anticoagulant rodenticide intoxication in a dog - PARDALI (Δ.Σ. ΠΑΡΔΑΛΗ) D. S.; ADΑMAMA-MORAITOU (Κ.Κ. ΑΔΑΜΑΜΑ-ΩΡΑΪΤΟΥ) K. K.; PATSIKAS (Μ.Ν. ΠΑΤΣΙΚΑΣ) M. N.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ) A. F. (Journal of the Hellenic Veterinary Medical Society, 2017)
A 3.5-year-old, spayed female, German shepherd-cross dog was presented with cough, hemoptysis, inspiratory stridor and fascial plane hematomas. Routine bleeding profile showed prolonged prothrombin time (PT) and partial thromboplastin time (PTT). Radiography revealed severe narrowing of tracheal lumen accompanied by increased thickness and opacity of its wall. Tracheal diameter was measured objectively, employing the ratio of its diameter (TD) to thoracic inlet distance (TI) and that of the midpoint between thoracic inlet and the carina (TT) to the 3r d rib width (3R), as well as the ratio of TT to predicted diameter of tracheal lumen [DPred (DPred cm = 0.47 (weight kg )0 3 9)]. All three ratios were found lower than normal. The space occupying effect of extensive and severe sub-mucosal hemorrhage due to anticoagulant rodenticide intoxication was incriminated.